RNA binding by Sxl proteins in vitro and in vivo. - Samuels, M E (1994)
Sxl has been proposed to regulate splicing of specific target genes by directly interacting with their pre-mRNAs. We have therefore examined the RNA-binding properties of Sxl protein in vitro and in vivo. Gel shift and UV cross-linking assays with a purified recombinant MBP-Sxl fusion protein demonstrated preferential binding to RNAs containing poly(U) tracts, and the protein footprinted over the poly(U) region. The protein did not appear to recognize either branch point or AG dinucleotide sequences, but an adenosine residue at the 5' end of the poly(U) tract enhanced binding severalfold. MBP-Sxl formed two shifted complexes on a tra regulated acceptor site RNA; the doubly shifted form may have been stabilized by protein-protein interactions. Consistent with its proposed role in pre-mRNA processing, in nuclear extracts Sxl was found in large ribonucleoprotein (RNP) complexes which sedimented significantly faster than bulk heterogeneous nuclear RNP and small nuclear RNPs. Anti-Sxl staining of polytene chromosomes showed Sxl protein at a number of chromosomal locations, among which was the Sxl locus itself. Sxl protein could also be targeted to a new chromosomal site carrying a transgene containing splicing regulatory sequences from the Sxl gene, following transcriptional induction. After prolonged heat shock, all Sxl protein was restricted to the heat-induced puff at the hs93D locus. In contrast, a presumptive small nuclear RNP protein was observed at several heat puffs following shock.